Avoiding path dependence of distributional weights: Lessons from climate change economic assessment - Disa Thureson (Örebro University School of Business, 2016)
In some cost benefit analysis (CBA) applications, such as those used for the valuation of climate change damage, distributional weights are used to account for diminishing utility of marginal income. This is usually done by means of intra-temporal distributional weights, which are combined with discounting to account for inter-temporal equity and efficiency. Here, I show that this approach might introduce some inconsistencies in terms of path dependence. In short, this inconsistency means that regional economic growth is double counted. This is because income weighting is performed both through the discount rate and through the distributional weights such that growth shows up twice in the weighting process. Using the PAGE2002 model, it is found that the inconsistency problem in the original model erases the influence of distributional weights on the social cost of carbon dioxide (SCCO2) compared to a standard CBA approach. The alternative approaches proposed here yield about 20%–40% higher values of SCCO2 than the old approach. While this has been briefly commented on in previous work, it has not yet been more thoroughly analyzed nor communicated to the broader community of climate policy and economic analysts who are not deeply interested in the specifications of the climate impact assessment models.
Keywords: C69; H23; H43; Q54; 330; Distributional weights; Equity weights; Discounting; Cost benefit analysis; Marginal utility; Integrated assessment model; PAGE2002; Social cost of carbon; Climate change